Organizing Prostitution Through Silence^Discourse: Unveiling Masks of a Masquerade. Issue 1 (1st January 2017) - Taylor, Julie L.; Canary, Heather E.
Abstract : Prostitution operates as a hidden organized activity relying on covert organizing processes in order to function. This study analyzes how both talk and silence discursively construct prostitution. Data, including prostitution policies and in-depth interviews, revealed that certain participants are marked silent while others are made visible. Results are presented through a metaphor of a masquerade in order to illuminate the complexity of hidden organizing. This metaphor offers a way to examine systematic and pervasive silence(s) within hidden organizing. Implications are offered for theory and research of the discursive construction of hidden organizations.